Water resources of Otrar region and the main problems with using them in agriculture (Journal of Geography and Environmental Management, 2019)
The article discusses the current state of surface and underground water of Otrar district, their sources of formation, themain problems associated with the water resources use and activities are shown. Also the features of the waterresources spread in the region and their spatial and economic value considered.